Case report: Carp edema virus infection in overwintering fish - Palikova, Miroslava; Balazova, Alena; Pojezdal, Lubomir; Papezikova, Ivana; Mikulikova, Ivana; Toulova, Ivona; Motlova, Jitka; Pikula, Jiri (Frontiers in Veterinary Science, 2025)
Carp Edema Virus (CEV) has emerged as a viral threat to the sustainability of European pond fisheries, with water temperature and stress playing a crucial role in disease outbreaks. Here, we report on a natural CEV infection in overwintering common carp (Cyprinus carpio; n = 1,160) broodstock that began to manifest clinically at an unusually low water temperature. In the initial outbreak phase, young broodstock fish exhibited abnormal activity and shoaling at the pond edge. While the water temperature under a discontinuous thin ice layer was 2°C, no deaths were observed. The first fish examined, using standard molecular methods for virological diagnosis, tested negative for CEV. Despite showing clinical signs suggestive of CEV infection, there was no gross pathology except for an increased amount of gill mucus, suggesting that CEV molecular detection may be dependent on infection progression. A shift from a period of cold stress to warming pond water temperatures may have influenced the subsequent progression of the disease. Ongoing clinical signs affected a large part of the population, which remained lethargic and gathered close to the banks. Subsequent virological testing performed ca. 3 weeks after the outbreak and first observation of clinically diseased fish detected the CEV genogroup I agent. CEV-driven die-offs occurred gradually as water temperatures increased to 8°C, with mortalities continuing for ca. 1 month. Interestingly, Přerov scaly carp and Hungarian mirror carp M2 strains differed significantly in mortality rates, at 30 and 60%, respectively. We tested a novel virus detection method, based on loop-mediated isothermal amplification (LAMP) of primers targeting the CEV genogroup I p4A gene, for applicability in the field. Samples from moribund fish, cadavers, and pond water all tested positive, with samples positive using LAMP subsequently confirmed by qPCR. To summarize, our data suggest it may be challenging to detect CEV DNA in both the first carp showing signs and surviving carp; scaly and scaleless carp show differential susceptibility to CEV infection; very low water temperatures of 2–4°C permit CEV infection in common carp; the LAMP method is applicable for rapid on-site CEV detection in clinical and environmental samples.